Morphology, topology and dimensions of the heart and arteries of genetically normal and mutant mouse embryos at stages S21–S23 - Geyer, Stefan H. (J Anat, 2017)
Accurate identification of abnormalities in the mouse embryo depends not only on comparisons with appropriate, developmental stage‐matched controls, but also on an appreciation of the range of anatomical variation that can be expected during normal development. Here we present a morphological, topological and metric analysis of the heart and arteries of mouse embryos harvested on embryonic day (E)14.5, based on digital volume data of whole embryos analysed by high‐resolution episcopic microscopy (HREM). By comparing data from 206 genetically normal embryos, we have analysed the range and frequency of normal anatomical variations in the heart and major arteries across Theiler stages S21–S23. Using this, we have identified abnormalities in these structures among 298 embryos from mutant mouse lines carrying embryonic lethal gene mutations produced for the Deciphering the Mechanisms of Developmental Disorders (DMDD) programme. We present examples of both commonly occurring abnormal phenotypes and novel pathologies that most likely alter haemodynamics in these genetically altered mouse embryos. Our findings offer a reference baseline for identifying accurately abnormalities of the heart and arteries in embryos that have largely completed organogenesis.